2011
DOI: 10.1002/eqe.1182
|View full text |Cite
|
Sign up to set email alerts
|

Rocking isolation of low‐rise frame structures founded on isolated footings

Abstract: SUMMARY This paper explores the effectiveness of a new approach to foundation seismic design. Instead of the present practice of over‐design, the foundations are intentionally under‐dimensioned so as to uplift and mobilize the strength of the supporting (stiff) soil, in the hope that they will thus act as a rocking–isolation mechanism, limiting the inertia transmitted to the superstructure, and guiding plastic ‘hinging’ into soil and the foundation–soil interface. An idealized simple but realistic one‐bay two‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(64 citation statements)
references
References 34 publications
1
62
0
1
Order By: Relevance
“…To do so, it was necessary to make the simplification of considering the pier as Use of Ricker motions as an alternative to pushover testing Loli, Knappett, Anastasopoulos and Brown rigid enough to respond predominantly through rocking and minimise flexural deformation of the column. This would be a valid assumption in the case of a relatively slender pier (H/B > 1·5) supported on a shallow foundation designed according to the principle of rocking isolation (see Gelagoti et al, 2012;Loli et al, 2014). In a few words, this refers to an underdesigned foundation (with FS E < 1) and a moment capacity lower than the capacity of the supported column section.…”
Section: Simplified Analytical Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…To do so, it was necessary to make the simplification of considering the pier as Use of Ricker motions as an alternative to pushover testing Loli, Knappett, Anastasopoulos and Brown rigid enough to respond predominantly through rocking and minimise flexural deformation of the column. This would be a valid assumption in the case of a relatively slender pier (H/B > 1·5) supported on a shallow foundation designed according to the principle of rocking isolation (see Gelagoti et al, 2012;Loli et al, 2014). In a few words, this refers to an underdesigned foundation (with FS E < 1) and a moment capacity lower than the capacity of the supported column section.…”
Section: Simplified Analytical Methodologymentioning
confidence: 99%
“…Anastasopoulos et al, 2010;Gajan and Kutter, 2008;Gajan et al, 2005;Gelagoti et al, 2012;Paolucci et al, 2007;Pecker, 2005). The key concept underpinning this design approach is that the moment capacity of the foundation is lower than that which causes damage to the supported column or pier, resulting in shallow foundations that are smaller than those produced by conventional design approaches (aiming to prevent inelastic foundation response).…”
Section: Introductionmentioning
confidence: 99%
“…Early research works focused on rigid block rocking on rigid base [3] or elastic/Winkler base [4,5], in which the influence of structure flexibility on dynamic response of structure is neglected. Later, calculation models for flexible blocks/structure rocking on rigid base [6,7] and elastic base [8,9] were proposed (see Figure 1). [4]; (c) flexible block rocking on rigid base [6]; (d) practical structure rocking on elastic base [8]; (e) SR model [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research studies on SSI have shown reduced seismic ductility demands of structures due to nonlinearity that arises mainly from the mobilization of the ultimate capacity and the uplifting response of shallow foundations. These studies have mainly focused on stiff slender structures on small foundations, such as shear walls [1], bridge piers [2,3], and framed structures [4,5] supported by spread footings. It has been found that the lifting off of one side of the footing not only results in geometric nonlinearity at the soil-footing interface, but causes yielding of soil on the other side, which in turn increases the uplift.…”
Section: Introductionmentioning
confidence: 99%